Potential vectors of Xylella fastidiosa in portuguese olive orchards: survey in Alentejo region and control measures - Neto, Ana Carina Marques (2020)
Tese de mestrado, Ecologia e Gestão Ambiental, Universidade de Lisboa, Faculdade de Ciências, 2017